A Novel, Cleaved Probe-Based Reverse Transcription Loop-Mediated Isothermal Amplification Method for Specific and Sensitive Detection of Porcine Deltacoronavirus - Shen, Haiyan; Wang, Songqi; Huang, Jun; Lin, Qijie; Zhang, Chunhong; Liu, Zhicheng; Zhang, Jianfeng; Liao, Ming (Frontiers in Veterinary Science, 2022)
Porcine deltacoronavirus (PDCoV) causes watery diarrhea, vomiting, and 30–40 % mortality in newborn piglets. A simple, rapid, and sensitive method for PDCoV detection is valuable in its surveillance and control. Here, we developed a novel, cleaved probe-based reverse transcription loop-mediated isothermal amplification (CP-RT-LAMP) method for PDCoV detection. A cleaved probe with a ribonucleotide insertion that targeted the N gene of PDCoV was designed. During the reaction, the enzyme ribonuclease H2 is activated only when the cleaved probe is perfectly complementary to the template, leading to the hydrolytic release of a quencher moiety and signal output. This method can be easily used on a real-time fluorescence quantitative equipment or an on-site isothermal instrument combined with a smartphone. The specificity assay showed no cross-reactivity with other porcine enteric pathogens. This method had a detection limit of 25 copies/µL, suggesting comparable sensitivity with reverse transcription quantitative PCR (RT-qPCR). In detecting 100 clinical samples (48 fecal swab specimens and 52 intestinal specimens), the detection rate of the CP-RT-LAMP method (26 %) was higher than that of RT-qPCR (17 %). Thus, it is a highly specific and sensitive diagnostic method for PDCoV, with a great application potential for monitoring PDCoV in the laboratory or point-of-care testing in the field.